Interactive Digital Teaching Materials Based on Numeracy: Development Studies on Statistical Material with The Context of Musi Banyuasin - Bariyah, Leny; Susanti, Ely; Aisyah, Nyimas (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Students' numeracy skills remain low, and some digital teaching materials are designed to support concentration and problem-solving through interactive features. In fact, students' Android devices have yet to be fully optimized for learning. This study aims to produce valid and practical digital teaching materials and to describe student responses after their use. The research followed the Plomp development model, consisting of four phases: preliminary investigation, design, realization, and test, evaluation, and revision. The subjects were 20 seventh-grade students from SMP Negeri 4 Jirak Jaya. Data were collected through questionnaires, observations, documentation, and interviews, and analyzed using descriptive quantitative and qualitative methods. The results show that the material is valid in terms of content, construction, language, and ICT, and is practical for use. Students' numeracy also improved to a good category. The digital material has potential effects on numeracy and is recommended for classroom use. Abstrak Kemampuan numerasi siswa masih rendah, dan beberapa materi pembelajaran digital dirancang untuk mendukung konsentrasi dan pemecahan masalah melalui fitur interaktif. Faktanya, perangkat Android siswa belum sepenuhnya dioptimalkan untuk pembelajaran. Studi ini bertujuan untuk menghasilkan materi pembelajaran digital yang valid dan praktis serta mendeskripsikan respons siswa setelah penggunaannya. Penelitian ini mengikuti model pengembangan Plomp, yang terdiri dari empat fase: preliminary investigation, design, realization, and test, evaluation, dan revision. Subjek penelitian adalah 20 siswa kelas tujuh dari SMP Negeri 4 Jirak Jaya. Data dikumpulkan melalui kuesioner, observasi, dokumentasi, dan wawancara, dan dianalisis menggunakan metode kuantitatif dan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa materi tersebut valid dari segi isi, konstruksi, bahasa, dan TIK, serta praktis untuk digunakan. Kemampuan numerasi siswa juga meningkat ke kategori baik. Materi digital tersebut memiliki potensi pengaruh terhadap kemampuan numerasi dan direkomendasikan untuk digunakan di kelas.